An Optimization Study of Lipid Extraction from Chlorella minutissima for Biodiesel Production - Anıl Tevfik Kocer; Benan İnan; Didem Özcimen (Journal of Chemical Engineering Research Updates, 2019)
Nowadays, researches on microalgal biodiesel production are focused on to improve the process efficiency and reduce the operational costs. One of the most expensive steps in microalgal biodiesel production is lipid extraction of microalgae. In this study, C. minutissima microalgae was produced in photobioreactor, and then solvent extraction of microalgal lipids were investigated. Box-Behnken design (BBD) was used to study the effect of extraction temperature, solvent/biomass ratio and residence time of solvent on the oil yield and to optimize lipid extraction. The maximum extraction yield was found to be 75% under the conditions of at the temperature of 70°C, 30:1 solvent/biomass ratio and 8 h. This study showed that the most effective parameter on extraction yield was temperature among three parameters. The results showed that optimized process conditions improved the extraction yield and it is a cost-effective way to produce biodiesel efficiently.